Cost of management of severe pneumonia in young children: systematic analysis - Zhang, Shanshan; Sammon, Peter M.; King, Isobel; Andrade, Ana Lucia; Toscano, Cristiana M.; Araujo, Sheila N; Sinha, Anushua; Madhi, Shabir A.; Khandaker, Gulam; Yin, Jiehui Kevin; Booy, Robert; Huda, Tanvir M; et al. (Journal of global health, 2016)
Childhood pneumonia is a major cause of childhood illness and the second leading cause of child death globally. Understanding the costs associated with the management of childhood pneumonia is essential for resource allocation and priority setting for child health. We conducted a systematic review to identify studies reporting data on the cost of management of pneumonia in children younger than 5 years old. We collected unpublished cost data on non-severe, severe and very severe pneumonia through collaboration with an international working group. We extracted data on cost per episode, duration of hospital stay and unit cost of interventions for the management of pneumonia. The mean (95% confidence interval, CI) and median (interquartile range, IQR) treatment costs were estimated and reported where appropriate. We identified 24 published studies eligible for inclusion and supplemented these with data from 10 unpublished studies. The 34 studies included in the cost analysis contained data on more than 95 000 children with pneumonia from both low- and-middle income countries (LMIC) and high-income countries (HIC) covering all 6 WHO regions. The total cost (per episode) for management of severe pneumonia was US$ 4.3 (95% CI 1.5-8.7), US$ 51.7 (95% CI 17.4-91.0) and US$ 242.7 (95% CI 153.6-341.4)-559.4 (95% CI 268.9-886.3) in community, out-patient facilities and different levels of hospital in-patient settings in LMIC. Direct medical cost for severe pneumonia in hospital inpatient settings was estimated to be 26.6%-115.8% of patients' monthly household income in LMIC. The mean direct non-medical cost and indirect cost for severe pneumonia management accounted for 0.5-31% of weekly household income. The mean length of stay (LOS) in hospital for children with severe pneumonia was 5.8 (IQR 5.3-6.4) and 7.7 (IQR 5.5-9.9) days in LMIC and HIC respectively for these children. This is the most comprehensive review to date of cost data from studies on the management of childhood pneumonia and these data should be helpful for health services planning and priority setting by national programmes and international agencies.